2013
DOI: 10.3109/15569527.2013.832688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic smoking on central corneal thickness, endothelial cell, and dry eye parameters

Abstract: Our results suggest that cigarette smoking seems to affect the Schirmer score, TBUT value, and hexagonal cells of the corneal endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
72
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 37 publications
12
72
2
Order By: Relevance
“…13 Some studies have reported an increased risk of guttata development and morphological changes in the corneal endothelium. 14,15 The contradicting results may be due to differences between the groups in these studies and not separating passive smokers. 16 The aim of our study was to compare corneal endothelial density and morphological changes Correspondence: Selcuk Kara, MD, Ç anakkale Onsekiz Mart Universitesi Tip Fakultesi, Goz Hastalıkları AD, Terziog lu Kampü sü , 17060, Ç anakkale, Turkey.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…13 Some studies have reported an increased risk of guttata development and morphological changes in the corneal endothelium. 14,15 The contradicting results may be due to differences between the groups in these studies and not separating passive smokers. 16 The aim of our study was to compare corneal endothelial density and morphological changes Correspondence: Selcuk Kara, MD, Ç anakkale Onsekiz Mart Universitesi Tip Fakultesi, Goz Hastalıkları AD, Terziog lu Kampü sü , 17060, Ç anakkale, Turkey.…”
Section: Introductionmentioning
confidence: 74%
“…18,19 Increased dry-eye signs and symptoms have also been shown in chronic smokers. 15,16 Chronic smoking disrupts the stability of the tear film on the corneal surface due to the negative effect on the cells that produce this film, leading to dry-eye symptoms. It is believed that the meibomian glands in the eyelids are especially affected and the TBUT is prolonged with the decrease in the lipid layer, which has an important role in delaying evaporation of tears.…”
Section: Discussionmentioning
confidence: 99%
“…The innermost endothelial layer of the cornea is a thin, monolayer of cuboidal cells covering the posterior side of Descemet's membrane which plays a key role in regulating the hydration level of the cornea through an active ATP and bicarbonate-dependent pump. Studies have reported that cigarette smoke affects endothelial cell count, guttata development, and morphological changes [27][28][29]. Corneal endothelial cells are sensitive to hypoxia and cigarette smoke-related hypoxia may put the endothelial cells at risk leading to corneal transplant failure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cigarette smoking may be harmful to the corneal endothelium. In our previous study, we found a significant decrease in the percentage of hexagonal cells in chronic smokers [1]. In addition to these findings, another study showed that smoking may inhibit or suppress the triggering factors of keratoconus and lead to a decreased rate or reduced severity of keratoconus [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic smoking has negative effects on the ocular surface; chronic smokers had lower Schirmer scores in the corneas [1], a higher degree of squamous metaplasia [2,3], a higher grade of lipid layer changes in tears [3], and lower tear film break-up time compared with non-smokers [1][2][3][4]. Smoking also affects tear secretion and protein components in tears [5,6].…”
Section: Introductionmentioning
confidence: 99%